Biblijne motywy i idee w twórczości Romana Brandstaettera - Mazan-Mazurkiewicz, Alicja (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2002)
The article concentrates on motifs and ideas of biblical origin in the post-war literary output of Roman Brandstaetter, presented at different textual levels. The author of the paper considers motifs which are the most frequent and significant for writer’s artistic visage, like the prodigal son, the sacrifice of Isaac, the fight against the angel, the abyss, the imitation of God, the incarnation. The aim is to describe the transformations of the motifs and the ideas, to trace them to their biblical source, and to interpret their functions in the texts. Brandstaetter’s work is interpreted in the light of the Catholic theology, the Christian tradition (included mysticism) and the whole text of the Bible, both Old and New Testament.